MUSICAL THEATER AND ENVIRONMENTAL POLITICS: ANALYSIS OF ENVIRONMENTAL DISCOURSES IN “DPR – MUSIKAL” (2021) - Sulaeman, Kirana Mahdiah; Mustofa, Mustabsyirotul Ummah (JWP (Jurnal Wacana Politik), 2024)
“DPR - Musikal” is a highly acclaimed and ambitious musical theater video created by SkinnyIndonesian24 (Jovial da Lopez & Andovi da Lopez) that features a compelling environmental message. This piece depicts the contested meaning of nature and how it is influenced by different interests in the DPR. This research will examine the environmental politics discourses present in “DPR - Musikal” as an artistic creation that establishes a connection between environmental concerns and the notion of power. The research employed a qualitative approach and utilized Critical Discourse Analysis (CDA) by Norman Fairclough. Data was gathered through video transcripts, direct interviews with informants (Jovial da Lopez), and additional documents. This research identifies two discourses in the piece: (1) sustainable development which reconciles the objectives of development agenda and environmental conservation, and (2) anti-capitalism which is identified through the narratives of land privatization, natural resources exploitation, and capitalism’s dominance in policymaking within the Indonesian parliament. These two discourses represent contrasting political thoughts, hence confirming incohesive solutions to the environmental problems. Although the producers condemn the dominance of business power and the exploitation of nature, they do not present a radical opposition to capitalism. Instead, they exhibit a lenient stance towards the development agenda, thus exemplifying the dominant influence of capitalist ideology within the musical theater production.